2021
DOI: 10.48550/arxiv.2107.06031
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vehicle Fuel Optimization Under Real-World Driving Conditions: An Explainable Artificial Intelligence Approach

Alberto Barbado,
Óscar Corcho

Abstract: Funding informationFuel optimization of diesel and petrol vehicles within industrial fleets is critical for mitigating costs and reducing emissions. This objective is achievable by acting on fuel-related factors, such as the driving behaviour style.In this study, we developed an Explainable Boosting Machine (EBM) model to predict fuel consumption of different types of industrial vehicles, using real-world data collected from 2020 to 2021. This Machine Learning model also explains the relationship between the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The significant advantages of EPS are also highlighted by environmental regulations. 19 The prospects for developing electronic control technology can be further explored in the direction of dynamic modelling of the steering system and the vehicle as a whole. Important factors include the rationality and precision of road comfort planning, the accuracy of stability control, and the effect of fail-safe steering strongly depends on the accuracy of model setting, degree, and precision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant advantages of EPS are also highlighted by environmental regulations. 19 The prospects for developing electronic control technology can be further explored in the direction of dynamic modelling of the steering system and the vehicle as a whole. Important factors include the rationality and precision of road comfort planning, the accuracy of stability control, and the effect of fail-safe steering strongly depends on the accuracy of model setting, degree, and precision.…”
Section: Discussionmentioning
confidence: 99%
“…The model used the dynamic characteristics of the steering resistance of the hydraulic steering system and the steering gear ratio. Barbado and Corcho, 19 specific trends in vehicle dynamics research were presented while underlining the need for an appropriate experimental research tool, a measurement, and a simulation platform. A platform concept was presented with a list of requirements concerning, among other things, the domain of virtual channels for online analysis and simulation, along with online validation of measurement methods and measuring devices.…”
Section: Introductionmentioning
confidence: 99%
“…Some of them fall under many categories, including those relating to drivers, weather, traffic, travel, and vehicles, among others. Barbado and Corcho (2021) evaluated the literature on a number of factors that might affect a vehicle's fuel consumption. Considering the effects related to travel factors, the authors identified eco-routing as a crucial element in reducing fuel consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the "black box" nature of ML makes it difficult to explain the relationship between input and output variables [12]. To address this issue, some propose the Explainable Boosting Machine (EBM) [13] and the Shapley Additive Explanations (SHAP) [14] algorithm to quantify the contribution of each input parameter to the output parameter, thus achieving the goal of explaining predictive models. Researchers have explored this problem; for example, Mangalathu et al [15] used the SHAP method to quantitatively analyze the impact of various parameters on the failure mode of shear walls based on existing models.…”
Section: Introductionmentioning
confidence: 99%